Developmental Psychopathology: An Interdisciplinary Approach to Mental Health - Ümit Morsünbül; Esma Nur Kaçıra; Şeyma Özdemİr (Psikiyatride Güncel Yaklaşımlar, 2019)
Nowadays, it’s seen that one-way perspectives have been replaced by a multidisciplinary perspective in the evaluation of mental health disorders. One of them is developmental psychopathology approach that examines disorders in many ways. In this review, it is tried to investigate the literature about how the developmental psychopathology approach is defined, the basic principles and how it provides perspectives while examine different issues. As a result, developmental psychopathology approach still provides new insights into the definition, prevention and treatment of mental health disorders, and also sheds light on mental health professionals in both academic and clinical areas.